2000
DOI: 10.1128/mcb.20.23.8958-8968.2000
|View full text |Cite
|
Sign up to set email alerts
|

Rdp1, a Novel Zinc Finger Protein, Regulates the DNA Damage Response of rhp51+ from Schizosaccharomyces pombe

Abstract: The Schizosaccharomyces pombe DNA repair gene rhp51؉ encodes a RecA-like protein with the DNAdependent ATPase activity required for homologous recombination. The level of the rhp51 ؉ transcript is increased by a variety of DNA-damaging agents. Its promoter has two cis-acting DNA damage-responsive elements (DREs) responsible for DNA damage inducibility. Here we report identification of Rdp1, which regulates rhp51؉ expression through the DRE of rhp51 ؉ . The protein contains a zinc finger and a polyalanine tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
0
7
1
Order By: Relevance
“…Microarray analysis has recently identified a Mec1-dependent gene expression signature in response to DNAdamaging agents that includes a large set of genes responsive to diverse environmental stresses (Gasch et al, 2001). A role for the DNA damage checkpoint pathway in regulating transcriptional responses to DNA-damaging agents has also been identified in fission yeast (Harris et al, 1996;Shim et al, 2000), although it is not known to what extent the checkpoint pathway coordinates damage-induced transcription in this microorganism.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Microarray analysis has recently identified a Mec1-dependent gene expression signature in response to DNAdamaging agents that includes a large set of genes responsive to diverse environmental stresses (Gasch et al, 2001). A role for the DNA damage checkpoint pathway in regulating transcriptional responses to DNA-damaging agents has also been identified in fission yeast (Harris et al, 1996;Shim et al, 2000), although it is not known to what extent the checkpoint pathway coordinates damage-induced transcription in this microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…In lower eukaryotes, studies with the budding yeast Saccharomyces cerevisiae have identified a large number of damageinduced genes, including many involved in DNA metabolism and DNA repair (Aboussekhra et al, 1996;Gasch et al, 2001). In the distantly related fission yeast Schizosaccharomyces pombe, rhp51 ϩ , uvi15 ϩ , uvi31 ϩ , UVDE ϩ , and rhp16 ϩ have been shown to be DNA damage inducible (Bang et al, 1996;Davey et al, 1997;Shim et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the wt strain we found up-regulation of the recombinational repair gene rhp51 (homolog to RAD51 of Saccharomyces cerevisiae) encoding a RecA-like protein whose DNA-dependent ATPase activity is required for homologous recombination. Thus, in S. pombe, recombinational repair is triggered by DDP as shown for a variety of DNA-damaging agents that increase the levels of the rhp51 transcript [34]. A putative damage-inducible deoxycytidyl transferase (SPBC1347.01c) possibly involved in mutagenic translesion DNA synthesis, was also induced by DDP.…”
Section: Ddp-induced Transcriptsmentioning
confidence: 99%